Zdolności motoryczne i budowa somatyczna 11-letnich uczniów ze Szkoły Podstawowej nr 2 w Płońsku = Motor skills and build somatic 11-year-old students from the Primary School No. 2 in Plonsk - Bieńkowska, Aleksandra; Cieślicka, Mirosława; Napierała, Marek; Zukow, Walery; Pabianek, Łukasz; Niespodziński, Bartłomiej; Sokołowska, Ewa; Kuska, Michalina; Pilewski, Robert; Zasada, Mariusz (Journal of Education, Health and Sport, 2015)
Bieńkowska Aleksandra, Cieślicka Mirosława, Napierała Marek, Zukow Walery, Pabianek Łukasz, Niespodziński Bartłomiej, Sokołowska Ewa, Kuska Michalina, Pilewski Robert, Zasada Mariusz. Zdolności motoryczne i budowa somatyczna 11-letnich uczniów ze Szkoły Podstawowej nr 2 w Płońsku = Motor skills and build somatic 11-year-old students from the Primary School No. 2 in Plonsk. Journal of Education, Health and Sport. 2015;5(5):292-299. ISSN 2391-8306. DOI 10.5281/zenodo.17743 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A292-299 https://pbn.nauka.gov.pl/works/560705 http://dx.doi.org/10.5281/zenodo.17743 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. Zdolności motoryczne i budowa somatyczna 11-letnich uczniów ze Szkoły Podstawowej nr 2 w Płońsku Motor skills and build somatic 11-year-old students from the Primary School No. 2 in Plonsk Aleksandra Bieńkowska, Mirosława Cieślicka, Marek Napierała, Walery Zukow, Łukasz Pabianek, Bartłomiej Niespodziński, Ewa Sokołowska, Michalina Kuska, Robert Pilewski, Mariusz Zasada Uniwersytet Kazimierza Wielkiego, Bydgoszcz Streszczenie Celem pracy było zapoznanie się ze stanem somatyki i zdolności motorycznych uczniów klas IV Szkoły Podstawowej nr 2 w Płońsku, oraz przeprowadzenie badań. Posłużono się Międzynarodowym Testem Sprawnościowym. Uczniowie podjęli się ośmiu prób, które wykonali w ciągu dwóch dni. Do zrealizowania celu wykonano również pomiary wzrostu i wagi ciała. Otrzymany materiał badawczy pozwolił na zapoznanie się z rozwojem somatycznym i zdolnościami motorycznymi uczniów klas IV Szkoły Podstawowej nr 2 w Płońsku. Dzięki rozmyślaniom na temat sprawności fizycznej i kalkulacji wyników przeprowadzonych badań wysunięto następujące wnioski: największa ilość dziewcząt posiada leptosomiczny typ sylwetki - 44%, reszta uczennic dysponuje atletyczną - 30%, oraz pykniczną budową ciała- 20%, wśród chłopców głównymi typami sylwetki są: pykniczny, który wynosi aż 37,5%, oraz atletyczny - 33%, natomiast najmniejsza ilość uczniów charakteryzuje leptosomiczny typ sylwetki, czyli 25%, średnia masy ciała wśród wszystkich uczniów to 42,28 kg na co składa się średnia masy ciała chłopców 43,5 i dziewcząt 41,7 kg. Słowa kluczowe: Międzynarodowy Test Sprawności Fizycznej, pomiary somatyczne, sprawność fizyczna. Abstract The aim was to familiarize themselves with the state somatics and motor skills of students of classes IV Elementary School No. 2 in Plonsk, and testing. The test was used International Cooperative Oncology. Students took on eight trials, which have done in two days. To achieve the objective measurements were also performed height and weight. The resulting research material allowed to familiarize themselves with the development of somatic and motor abilities of pupils of classes IV Elementary School No. 2 in Plonsk. With musings on physical fitness and calculating the results of the studies put forward the following proposals: the largest number of girls has leptosomic body type - 44%, the rest of the students have athletic - 30%, and a picnic body-building 20%, among boys the main types of profiles are: picnic, which is up 37.5%, and athletic - 33%, while the smallest number of pupils has leptosomic body type, or 25%; average body weight among all students is 42.28 kilograms on what makes up the average weight of boys and 43.5 girls 41.7 kg. Keywords: International Physical Fitness Test, somatic measurements, physical fitness.